New worlds of work: varieties of work in car factories in the BRIC countries - Jürgens, Ulrich; Krzywdzinski, Martin (New York, 2016)
"New industrial centres are emerging in the so-called BRIC countries (Brazil, Russia, India, and China), where large numbers of plants have been constructed in recent years, creating many manufacturing jobs. But what does industrial work look like in these locations? Up until now, much of the interest in developing country industrialization has concentrated on the poor working conditions that characterize some export-oriented sectors in emerging economies, most notoriously in the garment industry. In contrast, the concern of this book is with the modern facilities of multinational or local manufacturers that reflect aspirations for a process of industrial upgrading that might foreshadow the future for these countries.